Obrzęd bierzmowania w nauczaniu św. Augustyna - Żurek, Antoni (Vox Patrum, 2018)
St. Augustine did not write any text dedicated to the ceremony of confirmation. Nevertheless, in the Bishop of Hippo’s texts, it is possible to find some loose statements or allusions to that ceremony. There appeared mainly the terminology which was used to present the activities related to that sacrament dispensing. This article attempts to collect these statements, and basing on that, to reconstruct the ceremony itself and also its interpretation made by St. Augustine. The collected materials allow to make cautious conclusions. There is no doubt that confirmation was applied in the Hippo Church. However, it appears that St. Augustine’s cautiousness in confirmation-related statements was result of the disciplina arcani practice. Referring to that sacrament, he emphasised the presentation of the theological contents instead of the ceremony itself.